Effects of the “Internet +” nursing model based on user profiling on postoperative recovery in breast cancer: A prospective randomized controlled clinical trial - Xiuyuan Xie; Yuanfang Ren; Jia Yao; Yujie Fei; Fenghe Liu; Qian Tong; Juanjuan Huang; Meihong Kou; Cuifeng Jin; Weijuan Yang; Haiping Xu (International Journal of Nursing Sciences, 2025)
Objectives: This study aimed to explore the effectiveness and advantages of an “Internet +” nursing model based on user profiling in the rehabilitation of postoperative breast cancer patients. Methods: Breast cancer patients admitted to the hospital from July 2023 to September 2024 were enrolled. These patients were randomly assigned to a control group and an intervention group, with 52 patients in each group. The control group received routine nursing care, while the intervention group received an “Internet +” nursing intervention based on user profiling in addition to routine care. The intervention period lasted for one month following discharge. Before and one month after the intervention, the Fear of Progression Questionnaire-Short Form (FOP-Q-SF), the Fear of Cancer Recurrence Inventory-Short Form (FCRI-SF), Chinese Posttraumatic Growth Inventory (C-PTGI), and the Functional Assessment of Cancer Therapy-Breast (FACT-B) were applied to assess the effects of interventions. Results: A total of 104 patients were analyzed. After the intervention, FOP-Q-SF and FCRI-SF scores were significantly lower in the intervention group compared to the control group, with statistical significance (t = 3.98, P < 0.001; t = −7.59, P < 0.001), and Cohen’s d of 0.781 and 1.49, respectively. Additionally, C-PTGI and FACT-B scores in the intervention group were significantly higher than those in the control group (t = −6.534, P < 0.001; t = −4.579, P < 0.001), with Cohen’s d of 0.585 and 0.656. Conclusions: An “Internet +” nursing model based on user profiling could reduce postoperative breast cancer patients fear of disease progression and cancer recurrence, also enhancing posttraumatic growth and overall quality of life.